Disastri a confronto. Nuovi dati sulla cultura materiale e i traffici commerciali di Roma e Pompei tra la tarda età neroniana e l’età flavia - Ferrandes, Antonio Francesco; Pegurri, Alessandra (Rei Cretariae Romanae Fautorum Acta, 2024)
This contribution examines two documented contexts in the cities of Rome and Pompeii, linked to catastrophic events dating back to the late Neronian period. For Rome, the analysis focuses on deposits from the Colosseum valley, associated with construction activities initiated after the AD 64 fire for the construction of the Domus Aurea. In Pompeii, recently investigated soil layers at the Stabian Baths are explored, related to significant building modifications following seismic events before AD 79. Comparing these materials highlights similarities and differences between the two centers during this historical moment, including aspects like the general composition of archaeological deposits, relationships between local production and imports, and the external supply network. Notably, significant changes in interprovincial trade networks are observed, paving the way for commercial trends, including the growing influence of North African goods, persisting into late antiquity.